Knowledge and Attitude of Parents having Children with Febrile Seizure - Sadique, Zahir; Fatema Begum, Nurunnahar; Beauty, Anjuman Ara; Rahman Sarker, Md Ferdousur; Islam Bhuyian, Md Nazmul; Hossain, Md Mofazzol (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Febrile seizure is the most common seizure disorder among children less than 5 years of age. Observing a child experiencing a seizure is extremely traumatic experience for a parent. Many parents do not have any previous knowledge regarding febrile seizure and become anxious after the episode. Objectives: To study and understand the knowledge and attitude of parents whose children, aged between 6 months to 60 months, suffered from febrile seizure in Bangladesh. Materials and Methods: This prospective study was conducted by providing a structured, self-completed, closed-ended questionnaire to every parent whose child was admitted to the Paediatric indoor of Combined Military Hospital (CMH), Dhaka, Bangladesh from 1st March 2016 to 28th February 2017. Chisquare test was used to analyze the findings. Results: A total of 120 parents and children pairs participated in this study. Among these, 98 (81.7%) children had single seizure and the rest 22(18.3%) experienced more than one seizure episode. Only 20 (16.7%) parents knew that high fever could cause seizure in children. Thirty (25%) parents had thermometer in their house and 14 (11.7%) of them knew how to use thermometer properly. Most of the parents, 104 (86.7%) could not recognize seizure. When parents were asked about their concern regarding the impact of seizure on their affected child, 59 (49.2%) parents mentioned fear of having another attack and 24 (20%) parents included epilepsy. Ninety (75%) parents included their fear of another offspring to have the same disease and only 30 (25%) were not concerned about this. Conclusions: The parental fear of febrile seizure is a major concern among most of the parents whose child suffered from this. Parents need to receive appropriate information regarding febrile seizure. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 17-21